Acceptability and tolerability of liquid versus gel and standard versus virucidal alcohol-based hand rub formulations among dental students - Stauffer, Fritz; Griess, Marion; Pleininger, Gabriele; Zhumadilova, Anara; Assadian, Ojan (American Journal of Infection Control, 2013)
BackgroundHand hygiene is effective to prevent the transmission of microorganisms in health care settings, but compliance remains low, even when easy access to hand cleaning agents is provided. ObjectiveFormulation of alcohol-based hand rub (ABHRs) may influence staff compliance to hand hygiene. The aim of this prospective longitudinal study (1 week) was to investigate possible differences of 4 different gel or liquid ABHR formulations, with or without virucidal claim among dental students. MethodsParticipants were randomly assigned to dental treatment cubicles, equipped with either a gel or a liquid based ABHRs, with our without a virucidal claim. Participants assessed the subjective acceptability and the tolerability of test formulations on their hands over a period of 1 week using the 14 item, 7-point Lickert scale World Health Organization questionnaire. ResultsAll tested ABHRs passed the subjective acceptability criteria of ≥50% above 4 for the items “color and fragrance” and for all other items of >75% above 4 and may be regarded as “good.” Significant differences were observed between the 2 gels but not between the 2 liquid ABHRs. For subjective skin tolerability, no significant difference was observed between the liquid formulations after 1 consecutive week of application. However, the difference between the 2 gels was highly significant. ConclusionVirucidal ABHR formulations may be better accepted and tolerated over prolonged periods by dental students than anticipated. The user acceptability of ABHRs depend more on the specific product's formula than its general category.
Keywords: Hand hygiene; Epidemiology; Dentistry; Compliance; Comparison; WHO